Potential of hydrogel treatment in forest regeneration: impact on growth and vitality of Central European tree species - Tomášková, Ivana; Resnerová, Karolina; Trombik, Jiří; Bláha, Jaromír; Pastierovič, Filip; Macků, Jan (Frontiers in Forests and Global Change, 2023)
Drought negatively affects the growth and yield of plants. Several measures have been employed to improve the drought tolerance of plants, including the application of superabsorbent hydrogel (SAH) to soil. However, studies on the effect of SAH on trees in Central Europe, which has a temperate climate, are scarce. Here, the effects of SAH treatment on the cultivation of four key tree species in Central European forest ecosystems-European beech, sessile oak, Scots pine, and Norway sprucewere evaluated. Field and greenhouse experiments were conducted; the greenhouse conditions served as the reference for the absence of water stress. SAH treatment reduced seedling mortality by 1-9% in the field experiment. The morphological parameters of the control and SAH-treated seedlings did not significantly differ. Among the tree species, oak seedlings exhibited a positive response to SAH treatment. Spruce, pine, and beech did not respond to SAH treatment; the proline content of SAHtreated conifer leaves was three times higher than that of oak leaves but still very low, revealing no drought stress. The results highlight the significance of employing an individual approach in the application of SAH in forestry, rather than relying on generic measures.